Screening for Retinopathy of Prematurity in a Tertiary Ophthalmology Department in Turkey: Incidence, Outcomes, and Risk Factors - ÇERMAN, EREN; ÇELİKER ATABERK, HANDE; ERASLAN, MUHSİN; ŞAHİN, ÖZLEM (SLACK INC, 2014)
BACKGROUND AND OBJECTIVE: The aim of this study is to determine the incidence of retinopathy of prematurity (ROP), the number of preterm infants requiring treatment for ROP, and the factors influencing the development of ROP requiring treatment in a Turkish population. PATIENTS AND METHODS: Data on 1,252 infants who were screened for ROP in an ophthalmology department were retrospectively reviewed. Infants with a gestational age (GA) of no more than 28 weeks (n = 157) were designated group 1, those between 29 and 32 weeks (n = 572) were assigned to group 2, and those between 33 and 37 weeks (n = 523) were assigned to group 3. RESULTS: In group 1, ROP was detected in 70.0% of infants, 17.8% of whom required therapy. In group 2, ROP was detected in 41.4%, and 4.0% of those required therapy. In group 3, 18.1% were diagnosed with ROP, with 0.8% requiring treatment. CONCLUSION: Retinopathy of prematurity occurs, even among more mature infants, at a frequency that merits astute screening within parameters that reflect socioeconomic differences that appear to have an effect on the incidence.
Keywords: DEVELOPING-COUNTRIES; GUIDELINES; FREQUENCY; UNIT